Human Capital for Sustainable Development: A Conceptual Framework for Institutes of Higher Education - Khelghat-Doost, Hamoon; Sibly, Suzyrman (International Journal of Academic Research in Progressive Education and Development, 2020)
The role of higher education in navigating the development of human capital towards sustainability is vital. It is often argued that higher education should take the lead in training and educating the community and society for the cause of sustainability however, what is usually being ignored is the enhancement of the human capital within the higher education sector itself. In order to create a constructive relation between the higher education sector and the community for developing human capital, the higher education itself should adopt initiatives for developing its own human capital towards sustainability. This paper examines and argues the ways human capital in higher education sector (both administrative and academic staffs) can be trained and developed for sustainability. This approach would also enable the higher education sector to extend its sustainability outreach activities in developing the human capital beyond its borders. This paper therefore examines some of the most important elements in developing the human capital in higher education sector such as; personnel selection, development, motivation, policy, codes and auditing.